Advances in Virtual Agents and Affective Computing for the Understanding and Remediation of Social Cognitive Disorders - Jean-Claude Martin (Frontiers Research Topics, 2016)
Advances in modern sciences occur thanks to within-fields discoveries as well as confrontation of concepts and methods from separated, sometimes distant, domains of knowledge. For instance, the fields of psychology and psychopathology benefited from accumulated contributions from cognitive neurosciences, which, in turn, received insights from molecular chemistry, cellular biology, physics (neuroimaging), statistics and computer sciences (data processing), etc. From the results of these researches, one can argue that among the numerous cognitive phenomena supposedly involved in the emergence the human intelligence and organized behavior, some of them are specific to the social nature of our phylogenetic order. Scientific reductionism allowed to divide the social cognitive system into several components, i.e. emotion processing and regulation, mental state inference (theory of mind), agency, etc. New paradigms were progressively designed to investigate these processes within highly-controlled laboratory settings. Moreover, the related constructs were successful at better understanding psychopathological conditions such as autism and schizophrenia, with partial relationships with illness outcomes.